Aqueous leaf extract of Vitex negundo modulates M1-M2 phenotypic switch and functional changes in human macrophages in an in vitro model of hypertension - Boniface Makori Nyamweya; Dilani Rukshala; Rajiva De Silva; Sunil Premawansa; Narmada Fernando; Shiroma Handunnetti (Journal of Ayurveda and Integrative Medicine, 2025)
Background: Inflammation and oxidative stress are key drivers of hypertension. Vitex negundo L. is a medicinal plant used in Ayurveda and has potential anti-inflammatory effects. Objectives: This study aims to assess the immunomodulatory effects of aqueous mature leaf extract (ALE) of V. negundo in an in vitro model of hypertension. Materials and methods: Non-toxic concentrations of ALE were selected using SRB and MTT assays. Quantitative NBT and Griess assays were done to assess the effect of the ALE on Ang-II-induced production of reactive oxygen species (ROS) and reactive nitrogen species (RNS) respectively. The effect of ALE of V. negundo on the expression of tumor necrosis factor-alpha, interleukin 6, interleukin 1 beta and nuclear factor kappa B were assessed using RT-qPCR. Expression of M0, M1 and M2 surface markers were assessed using flow cytometry. Results: ALE of V. negundo inhibited the production ROS and RNS in a dose-dependent manner comparable with Telmisartan drug control (p < 0.0001). Ang-II activated, THP-1 derived macrophages expressed high levels of M1 markers. Interestingly, the pre-treatment of Ang-II-activated, THP-1 derived macrophages with ALE of V. negundo increased the expression of M2 marker as CD206high (89.63%) but no increase in CD163-moderate (27.1%). Both ALE of V. negundo and Telmisartan down-regulated the expression of the pro-inflammatory cytokines in the hypertension model (p < 0.0001). Conclusions: The results suggest the potential of ALE of V. negundo in exerting immunomodulatory effects in an in vitro model of angiotensin II-mediated hypertension mainly by modulating M1-M2 macrophage switch and limiting inflammation and production of pro-oxidants.